Covid-19 and Growth Hormone/Insulin-Like Growth Factor 1: Study in Critically and Non-Critically Ill Patients - Ilias, Ioannis; Diamantopoulos, Aristidis; Botoula, Efthymia; Athanasiou, Nikolaos; Zacharis, Alexandros; Tsipilis, Stamatios; Jahaj, Edison; Vassiliou, Alice G.; Vassiliadi, Dimitra A.; Kotanidou, Anastasia; Tsagarakis, Stylianos; Dimopoulou, Ioanna (Frontiers in Endocrinology, 2021)
Objective We aimed to measure insulin-like growth factor 1 (IGF1) and growth hormone (GH) in critically and non-critically ill patients with Covid-19 and assess them vis-a-vis clinical and laboratory parameters and prognostic tools. Subjects & Methods We included patients who were admitted to the wards or the ICU of the largest Covid-19 referral hospital in Greece; patients with non-Covid-19 pneumonia served as controls. Apart from the routine laboratory work-up for Covid-19 we measured GH and IGF1 (and calculated normalized IGF-1 values as standard deviation scores; SDS), after blood sampling upon admission to the wards or the ICU. Results We studied 209 critically and non-critically ill patients with Covid-19 and 39 control patients. Patients with Covid-19 who were ICU non-survivors were older and presented with a worse hematological/biochemical profile (including white blood cell count, troponin, glucose, aminotransferases and lactate dehydrogenase) compared to ICU survivors or Covid-19 survivors in the wards. Overall, IGF-1 SDS was higher in Covid-19 survivors compared to non-survivors (-0.96+1.89 vs -2.05+2.48, respectively, p=0.030). No significant differences were noted in GH between the groups. Nevertheless, in critically ill patients with Covid-19, the prognostic value of IGF-1 (raw data), IGF-1 (SDS) and GH for survival/non-survival was on a par with that of APACHE II and SOFA (with a marginal difference between GH and SOFA). Conclusion In conclusion, our findings suggest that there might be an association between low IGF1 (and possibly GH) and poor outcome in patients with Covid-19.